Optimalisasi Canva Sebagai Media Pembelajaran Berbasis Animasi 2D di Kalamullah Qur’an and Multilingual School, Pattani Thaland - Azim, Fauzan; Anshari, Khairul; Effendi, Noverta; Farida, Fitri; Ramadhani, Witri; Hayati, Zuqriva (Jurnal Pengabdian UntukMu NegeRI, 2024)
Technology in education is needed as a learning medium that is used as a communication link between students and teachers. One application that can be used is Canva. The aim of this service is to introduce the Canva application and provide training and assistance to students, teachers and education staff in using the Canva application so that the learning process is more interesting and better. Training/counseling activities are carried out using training and workshops using laptops and smartphones equipped with video tutorials that have been prepared on YouTube. Providing workshops and training was successful in using the Canva application for teachers, education staff and students at Kalamullah Qur'an and Multilingual School Pattani Thailand. Using the Canva application can make it easier to design learning media in the form of 2D animation. Keywords: Learning Media, Canva Application, 2D Animation